Assessment of thermal conductivity and indoor air quality of fired clay brick incorporated with electroplating sludge - Abdul Kadir, Aeslina; Detho, Amir; Hashim, Azini Amiza; Mat Rozi, Nur Hidayah (Elsevier, 2023)
Industrial activity is one of the main contributors in developing and growth of economy in Malaysia. Industries and agricultures in Malaysia, generate harmful waste which, if not properly disposed of can damage to landfills and the environment. Brick is one of an important masonry unit needed as building materials. This paper addresses the thermal conductivity and Indoor Air Quality (IAQ) when the fired clay bricks are combined with electroplating sludge (ES). The fired clay bricks were examined using five different ratios 2%, 4%, 6%, 8% and 10%. The X-ray Fluorescence (XRF) result showed that the highest percentage of electroplating sludge composition was aluminium oxide (Al2O3) which is 67.20%. The clay soil showed that the highest percentage of silicon dioxide (SiO2) and aluminium oxide (Al2O3) which was 67.60% and 19.70%, respectively. The IAQ result of carbon dioxide (CO2), carbon monoxide (CO), ozone (O3), formaldehyde (HCHO) and particulate matter (PM10) of fired clay brick with 4% of electroplating sludge was acceptable and safe to be used as building material as it had the most lower gas emissions and compared to the control brick with 0% of sludge. Moreover, all parameters in every pattern did not have much contrast with the limit by Industry Code of Practice on Indoor Air Quality (ICOP-IAQ) standard. Therefore, electroplating sludge an alternative low-cost material that provides an environmentally friendly disposal method.